Growth of magnesium oxide nanoparticles onto graphene oxide nanosheets by sol-gel process - Lee, Ju Ran; Koo, Hye Young (KOREAN CARBON SOC, 2013)
Nanocomposites comprised of graphene oxide (GO) nanosheets and magnesium oxide (MgO) nanoparticles were synthesized by a sol-gel process. The synthesized samples were studied by X-ray powder diffraction, atomic force microscopy, transmission electron microscopy, and energy-dispersive X-ray analysis. The results show that the MgO nanoparticles, with an average diameter of 70 nm, are decorated uniformly on the surface of the GOs. By controlling the concentration of the MgO precursors and reaction cycles, it was possible to control the loading density and the size of the resulting MgO particles. Because the MgO particles are robustly anchored on the GO structure, the MgO/GOs nanocomposites will have future applications in the fields of adsorption and chemical sensing.
Keywords: MGO